(D)-p-Hydroxyphenylglycine production by thermostable D-hydantoinase from Brevibacillus parabrevis-PHG1. (February 2013) - Nandanwar, Hemraj S.; Prajapati, Rajnikant; Hoondal, Gurinder S.
Abstract This study was aimed at the investigation of D-hydantoinase from newly isolated strains of bacteria for overproduction of D-p-hydroxyphenylglycine. It was also hoped to develop a D-hydantoinase with suitable physicochemical parameters to make a successful process for other D-amino acids. D-hydantoinase was isolated from a Gram positive bacterial strain PHG1, identified as Brevibacillus parabrevis based on 16S rRNA gene sequence analysis. The strain showed hydantoinase activity of 5.0 U/ml of broth with hydantoin as substrate, at a cell turbidity of 4.8 at 600 nm. The enzyme was purified to homogeneity with native and subunit molecular mass of ≈154 kDa and ≈43 kDa, respectively. The specific activity of the enzyme was found to be ≈750 μmole/min/mg. D, L-p-hydroxyphenylhydantoin was found to be the preferred substrate after unsubstituted hydantoin. The optimum temperature and pH for enzyme activity were 70°C and 8.5, respectively, with a half-life of 120 min at 70°C. Supplementing with 0.32 mM Mn2+ in the growth medium resulted in ≈3-fold increase in enzyme activity. Ninety-five percent conversion efficiency of D-hydantoinase for D, L-p-hydroxyphenylhydantoin (10% w/v) into N-carbamoyl-(D)-p-hydroxyphenylglycine, better pH-temperature stability and broad substrate specificity signify the usefulness of this enzyme for production of D-p-hydroxyphenylglycine and other D-amino acids of industrial importance.